Compact slot antenna with rectangular-ring tuning stub for ultra-wideband application - Kueathaweekun, W.; Anantrasirichai, N.; Benjangkaprasert, C.; Wakabayashi, T. (My University, 2009)
A compact microstrip-fed slot antenna with rectangular-ring tuning stub for ultra-wideband application is presented. The characteristics of antenna are proposed and analyzed for instance return loss, bandwidth, and far field radiation patterns. The measurement results of the impedance matching for the proposed antenna show the impedance bandwidth of 120% of the center band (3.09-12.15GHz), determined by -10 dB return loss. The measured radiation patterns are bi-directional and average gain is 3.5 dBi.